Optimization of the protocrystalline p-layer in a-Si:H-based n-i-p photodiodes. Issue 1666 (21st July 2014) - Vygranenko, Y.; Fernandes, M.; Vieira, M.; Sazonov, A.
ABSTRACT: This work reports a carbon-free, blue-enhanced a -Si:H n-i-p photodiode with an optimized protocrystalline p -layer. Although the used deposition conditions for the p -layer correspond to the microcrystalline regime, thin layers are mostly protocrystalline due to the amorphous underlying undoped layer. This conclusion is supported by Raman spectroscopy measurements. We have also found that the optical band gap of the p -layer can be varied by adjusting the rf power. By widening the band gap and tuning the impurity concentration in the p -layer, absorption and recombination losses at the p-i interface were reduced. The current-voltage, capacitance-voltage, and spectral-response characteristics of fabricated photodiodes are correlated with the doping level, optical band gap, and deposition conditions for p -layers. The optimized device exhibits a leakage current of about ∼80 pA/cm 2 at 5 V reverse bias. The external quantum efficiency reaches a peak value of 92% at a wavelength of 510 nm, and, at shorter wavelengths, decreases down to 66%@400nm.